Anti-aging piezoelectric cable
By adding modified magnesium hydroxide and anti-aging agent to the polypropylene outer sheath, the aging problem of the polypropylene outer sheath under light, heat and oxygen is solved, and the aging resistance and flame retardant performance is improved, satisfying the satisfaction of High performance needs in the field of wire and cable technology.
Patent Information
- Application Number
- CN202411422312.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The polypropylene outer sheath is prone to aging and degradation under the action of light, heat and oxygen, resulting in poor aging resistance and cannot meet the higher demand in the field of wire and cable technology.
Using polypropylene resin as the outer sheath material, modified magnesium hydroxide and anti-aging agent are added, and compatibility with polypropylene is improved through modification treatment, and antioxidants and lubricants are added to the outer sheath to form resistance. Aging piezoelectric cables.
It significantly enhances the flame retardant and aging resistance of the cable, improves the mechanical properties, has long-term and stable performance, is not easy to fall off, and has important application value.
Smart Images

Figure BDA0005081166680000031 
Figure BDA0005081166680000032 
Figure BDA0005081166680000041
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electric wires and cables, and in particular, relates to an aging-resistant piezoelectric cable. Background Art
[0002] The structure of a piezoelectric cable usually includes conductors, insulators, metal tapes, outer sheaths, etc. The outer sheath is in direct contact with the external environment and plays a decisive role in the performance of the cable. Common outer sheaths include polyethylene, cross-linked polyethylene, polypropylene, fluoroplastics, and silicone rubber. Among them, polypropylene has excellent insulation performance, high temperature resistance, light weight, easy processing, and recyclability. It is widely used due to its excellent performance. However, polypropylene also has certain shortcomings. Due to the presence of a large number of unstable tertiary carbon atoms in the polypropylene chain, it is prone to aging and degradation after being exposed to light, heat, and oxygen, and has poor aging resistance. Therefore, it is urgent to invent an aging-resistant piezoelectric cable to meet the higher demands in the field of wire and cable technology. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects of the prior art and provide an aging-resistant piezoelectric cable.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] An aging-resistant piezoelectric cable consists of a conductor, an insulating layer, a metal shielding layer and an outer sheath which are arranged in sequence from the inside to the outside.
[0006] Furthermore, the material of the conductor is pure copper.
[0007] Furthermore, the material of the insulating layer is polyethylene.
[0008] Furthermore, the metal shielding layer is woven from copper wires.
[0009] Furthermore, the material of the outer sheath includes the following raw materials in parts by weight: 60-80 parts of polypropylene resin, 15-25 parts of modified magnesium hydroxide, 4-16 parts of anti-aging agent, 0.1-0.3 parts of initiator, and 3-6 parts of lubricant.
[0010] Furthermore, the initiator is one of benzoyl peroxide and lauroyl peroxide.
[0011] Furthermore, the lubricant is one of epoxidized soybean oil and paraffin.
[0012] Further, the modified magnesium hydroxide is prepared by the following steps:
[0013] At room temperature, magnesium hydroxide and deionized water are stirred at high speed for 45 minutes in a high shear mixing emulsifier, γ-aminopropyltriethoxysilane (silane coupling agent KH-550) is added, and the mixture is stirred at high speed for 45 minutes in a high shear mixing emulsifier. After the reaction is completed, the mixture is filtered and dried in vacuum to obtain modified magnesium hydroxide.
[0014] Furthermore, the ratio of magnesium hydroxide, deionized water, and γ-aminopropyltriethoxysilane is 5.0 g:100 mL:7.5 g.
[0015] Magnesium hydroxide is an inorganic flame retardant with good flame retardant and smoke suppression properties. Using silane coupling agent KH-550 to modify magnesium hydroxide can greatly improve the interface effect between magnesium hydroxide and polypropylene matrix, improve the compatibility of magnesium hydroxide with the matrix, thereby promoting the uniform dispersion of modified magnesium hydroxide in the matrix, reducing agglomeration, and giving full play to the flame retardant and smoke suppression properties of magnesium hydroxide.
[0016] Furthermore, the anti-aging agent is prepared by the following steps:
[0017] S1. In a three-necked flask equipped with a stirring device, 2,2,6,6-tetramethylpiperidinol, n-octane and molybdenum trioxide were mixed and stirred uniformly, heated to 85°C, and tert-butyl hydroperoxide aqueous solution was added dropwise. After the addition was completed, the reaction was refluxed for 8 hours. After the reaction was completed, the filtrate was filtered, activated carbon was added to the filtrate and stirred for 1 hour, the mixture was allowed to stand, filtered, and the filtrate was taken. The n-octane was removed by vacuum distillation to obtain intermediate 1; the ratio of the amount of 2,2,6,6-tetramethylpiperidinol, n-octane, molybdenum trioxide and tert-butyl hydroperoxide aqueous solution was 15.7 g:20.3 g:0.2 g:10 mL;
[0018] Under the catalysis of molybdenum trioxide and the oxidation of tert-butyl hydroperoxide, 2,2,6,6-tetramethylpiperidinol and n-octane undergo a free radical coupling reaction; n-octane serves as both a reactant and a reaction solvent, which can reduce the formation of by-products to obtain intermediate 1; the specific reaction process is as follows:
[0019]
[0020] S2. In a three-necked flask equipped with a thermometer, an electromagnetic stirrer and a spherical condenser, a drying tube is added to the outlet of the condenser, and the drying tube is connected to a tail gas absorption device to absorb the generated hydrogen chloride gas. After pentaerythritol and benzene are mixed, phosphorus trichloride is slowly added dropwise under stirring, and the temperature is controlled not to exceed 25° C. After the addition is completed, the reaction temperature is controlled to 75° C., and the reflux reaction is carried out for 4 hours. After the reaction is completed, the solvent benzene and excess phosphorus trichloride are distilled off to obtain intermediate 2; the ratio of pentaerythritol, benzene and phosphorus trichloride is 13.6 g:100 mL:28.1 g;
[0021] Pentaerythritol reacts with phosphorus trichloride to obtain intermediate 2; the specific reaction is as follows:
[0022]
[0023] S3, in a three-necked flask equipped with a stirring device, the intermediate 2, the intermediate 1, potassium carbonate (acid binding agent) and N, N-dimethylformamide (DMF) were mixed and stirred uniformly, the reaction temperature was controlled to 70°C, and the reaction was kept warm for 6 hours. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:2), and the eluent was removed by rotary evaporation to obtain intermediate 3; the ratio of the amount of intermediate 2, intermediate 1, potassium carbonate and N, N-dimethylformamide was 27.7 g:28.5 g:13.8 g:150 mL;
[0024] Under the catalysis of potassium carbonate, intermediate 2 and intermediate 1 react, and by controlling the molar ratio of the two to be close to 1:1 and a slight excess of intermediate 2, only one chlorine group on intermediate 2 participates in the reaction to obtain intermediate 3; the specific reaction process is as follows:
[0025]
[0026] S4. In a three-necked flask equipped with a stirring device, the intermediate 3, 3-butene-1-ol, potassium carbonate and N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 75°C, and the reaction was kept warm for 8 hours. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:3), and the eluent was removed by rotary evaporation to obtain an antioxidant; the ratio of the amount of intermediate 3, 3-butene-1-ol, potassium carbonate, and N,N-dimethylformamide was 51.3g:7.2g:13.8g:150mL;
[0027] Potassium carbonate is used as an acid-binding agent to remove the hydrogen chloride generated by the reaction, and the intermediate 3 and 3-butene-1-ol undergo a nucleophilic substitution reaction to obtain an antioxidant. The specific reaction process is as follows:
[0028]
[0029] The prepared antioxidant molecule contains phosphite, which can be used as a kind of auxiliary antioxidant to decompose the hydroperoxide generated in the polymer due to oxidative aging, making it inactive, thereby achieving the purpose of terminating or delaying the oxidative degradation of the polymer and improving the aging resistance of the matrix; in addition, the hindered amine in the antioxidant molecule will decompose hydrogen dioxide to produce stable nitroxide free radicals, which can very effectively capture the free radicals generated in the photo-oxidative degradation, effectively inhibit the photo-oxidative degradation of the matrix, and can be regenerated under stable conditions, and can play a synergistic role with phosphite to greatly enhance the aging resistance of the matrix; finally, the introduced long carbon chain belongs to the methylene chain segment, which is a flexible chain segment, can improve the mechanical properties of the matrix to a certain extent, and can be interspersed in the molecular chain of the matrix to improve the stability of the antioxidant molecule;
[0030] It should be noted that one end of the antioxidant molecule also contains a carbon-carbon double bond, which can cross-link with the matrix, thereby improving the migration and exudation resistance of the antioxidant small molecule and making the performance of the antioxidant stable for a long time.
[0031] Beneficial effects of the present invention:
[0032] The cable prepared by the present invention has an outer sheath material with polypropylene as the matrix, and modified magnesium hydroxide and an anti-aging agent are added, wherein the modified magnesium hydroxide has better compatibility with the polypropylene matrix than ordinary magnesium hydroxide, and the agglomeration phenomenon is significantly reduced, which can greatly enhance the flame retardant performance of the cable; in addition, the prepared anti-aging agent can significantly enhance the aging resistance and a certain degree of mechanical properties of the cable, and the performance is long-term and stable, and it is not easy to fall off. Therefore, the cable prepared by the present invention has excellent flame retardant performance, stable and efficient aging resistance and a certain degree of mechanical strength, and has important application value in the field of wire and cable technology. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] Preparation of anti-aging agent:
[0036] S1. In a three-necked flask equipped with a stirring device, 15.7 g of 2,2,6,6-tetramethylpiperidinol, 20.3 g of n-octane, and 0.2 g of molybdenum trioxide were mixed and stirred evenly, heated to 85°C, and 10 mL of tert-butyl hydroperoxide aqueous solution (mass fraction 18%) was added dropwise. After the addition was completed, the reaction was refluxed for 8 h. After the reaction was completed, the filtrate was filtered, activated carbon was added to the filtrate, and stirred for 1 h. The mixture was allowed to stand, filtered, and the filtrate was taken. The n-octane was removed by vacuum distillation to obtain intermediate 1.
[0037] S2, in a three-necked flask equipped with a thermometer, an electromagnetic stirrer and a spherical condenser, and a drying tube is added to the outlet of the condenser, the drying tube is connected to a tail gas absorption device to absorb the generated hydrogen chloride gas, 13.6g of pentaerythritol and 100mL of benzene are mixed, and 28.1 of phosphorus trichloride is slowly added dropwise under stirring, and the temperature is controlled not to exceed 25°C. After the addition is completed, the reaction temperature is controlled to 75°C, and the reaction is refluxed for 4h. After the reaction is completed, the solvent benzene and excess phosphorus trichloride are removed by distillation to obtain intermediate 2;
[0038] S3, in a three-necked flask equipped with a stirring device, 27.7g of intermediate 2, 28.5g of intermediate 1, 13.8g of potassium carbonate and 150mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 70°C, and the reaction was kept warm for 6h. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:2), and the eluent was removed by rotary evaporation to obtain intermediate 3;
[0039] S4. In a three-necked flask equipped with a stirring device, 51.3 g of intermediate 3, 7.2 g of 3-butene-1-ol, 13.8 g of potassium carbonate and 150 mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 75°C, and the reaction was kept warm for 8 hours. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation. Then it was purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:3), and the eluent was removed by rotary evaporation to obtain an anti-aging agent.
[0040] Example 2
[0041] Preparation of anti-aging agent:
[0042] S1. In a three-necked flask equipped with a stirring device, 31.4 g of 2,2,6,6-tetramethylpiperidinol, 40.6 g of n-octane and 0.4 g of molybdenum trioxide were mixed and stirred evenly, heated to 85°C, and 20 mL of tert-butyl hydroperoxide aqueous solution (mass fraction 18%) was added dropwise. After the addition was completed, the reaction was refluxed for 8 h. After the reaction was completed, the filtrate was filtered, activated carbon was added to the filtrate and stirred for 1 h, the mixture was allowed to stand, filtered, the filtrate was taken, and the n-octane was removed by vacuum distillation to obtain intermediate 1;
[0043] S2, in a three-necked flask equipped with a thermometer, an electromagnetic stirrer and a spherical condenser, and a drying tube is added to the outlet of the condenser, the drying tube is connected to a tail gas absorption device to absorb the generated hydrogen chloride gas, 27.2g of pentaerythritol and 200mL of benzene are mixed, and 56.2 of phosphorus trichloride is slowly added dropwise under stirring, and the temperature is controlled not to exceed 25°C. After the addition is completed, the reaction temperature is controlled to 75°C, and the reaction is refluxed for 4h. After the reaction is completed, the solvent benzene and excess phosphorus trichloride are distilled off to obtain intermediate 2;
[0044] S3, in a three-necked flask equipped with a stirring device, 55.4g of intermediate 2, 57g of intermediate 1, 27.6g of potassium carbonate and 300mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 70°C, and the reaction was kept warm for 6h. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:2), and the eluent was removed by rotary evaporation to obtain intermediate 3;
[0045] S4. In a three-necked flask equipped with a stirring device, 102.6 g of intermediate 3, 14.4 g of 3-butene-1-ol, 27.6 g of potassium carbonate and 300 mL of N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 75°C, and the reaction was kept warm for 8 hours. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation. Then it was purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:3), and the eluent was removed by rotary evaporation to obtain an anti-aging agent.
[0046] Example 3
[0047] Preparation of modified magnesium hydroxide:
[0048] At room temperature, 5.0 g of magnesium hydroxide and 100 mL of deionized water were stirred at high speed for 45 min in a high shear mixing emulsifier, 7.5 g of γ-aminopropyltriethoxysilane was added, and the mixture was stirred at high speed for 45 min in a high shear mixing emulsifier. After the reaction was completed, the mixture was filtered and dried in vacuo to obtain modified magnesium hydroxide.
[0049] Example 4
[0050] Preparation of modified magnesium hydroxide:
[0051] At room temperature, 10.0 g of magnesium hydroxide and 200 mL of deionized water were stirred at high speed for 45 min in a high shear mixer, 15.0 g of γ-aminopropyltriethoxysilane was added, and the mixture was stirred at high speed for 45 min in a high shear mixer. After the reaction was completed, the mixture was filtered and dried in vacuo to obtain modified magnesium hydroxide.
[0052] Example 5
[0053] Preparation of outer sheath material:
[0054] 60 g of polypropylene resin, 15 g of modified magnesium hydroxide prepared in Example 3, 4 g of the anti-aging agent prepared in Example 1, 0.1 g of benzoyl peroxide and 3 g of epoxidized soybean oil were put into a twin-screw extruder, melt-blended and extruded to obtain an outer sheath material.
[0055] Example 6
[0056] Preparation of outer sheath material:
[0057] 70 g of polypropylene resin, 20 g of modified magnesium hydroxide prepared in Example 4, 10 g of the anti-aging agent prepared in Example 2, 0.2 g of lauroyl peroxide and 4 g of paraffin were put into a twin-screw extruder, melt-blended and extruded to obtain an outer sheath material.
[0058] Example 7
[0059] Preparation of outer sheath material:
[0060] 80 g of polypropylene resin, 25 g of modified magnesium hydroxide prepared in Example 4, 16 g of the anti-aging agent prepared in Example 2, 0.3 g of lauroyl peroxide and 6 g of paraffin were put into a twin-screw extruder, melt-blended and extruded to obtain an outer sheath material.
[0061] Example 8
[0062] Polyethylene is extruded on a pure copper conductor to form an insulating layer; a metal shielding layer woven with copper wire is coated on the surface of the insulating layer; then 80g of polypropylene resin, 25g of modified magnesium hydroxide prepared in Example 4, 16g of an anti-aging agent prepared in Example 2, 0.3g of lauroyl peroxide and 6g of paraffin are put into a twin-screw extruder, melt-blended, and coated on the surface of the metal shielding layer through an extruder to obtain an aging-resistant piezoelectric cable.
[0063] Comparative Example 1
[0064] A commercially available phosphite antioxidant of equal quality was used to replace the anti-aging agent in Example 7, and the remaining steps were the same as in Example 7 to obtain an outer sheath material.
[0065] Comparative Example 2
[0066] Commercially available polypropylene cable material was used.
[0067] The materials of Examples 5-7 and Comparative Examples 1-2 were made into corresponding shapes to be tested according to different test standards, and the following performance tests were performed:
[0068] The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to determine the limiting oxygen index of the sample;
[0069] The tensile properties are determined using the national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics";
[0070] The notched impact strength of the sample was measured using the national standard GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics";
[0071] The sample was placed in a xenon lamp aging test chamber for accelerated aging for 14 days. The aging conditions were air atmosphere, xenon lamp wavelength 280-800nm, and irradiation intensity 550W / m 2 , determine the tensile strength after aging (GB / T1040.2-2006), and calculate the tensile strength retention rate; tensile strength retention rate = tensile strength after test / tensile strength before test × 100%;
[0072] The measurement results are shown in the following table:
[0073]
[0074] It can be seen from the above table that the outer sheath material prepared in the embodiment of the present invention has higher aging resistance and mechanical strength than the comparative example, and has good flame retardant properties, and has important application value in the field of wire and cable technology.
[0075] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0076] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. An aging-resistant piezoelectric cable, comprising a conductor, an insulating layer, a metal shielding layer and an outer sheath arranged in sequence from the inside to the outside, characterized in that: The material of the outer sheath comprises the following raw materials in parts by weight: 60-80 parts of polypropylene resin, 15-25 parts of modified magnesium hydroxide, 4-16 parts of anti-aging agent, 0.1-0.3 parts of initiator, and 3-6 parts of lubricant.
2. The aging-resistant piezoelectric cable according to claim 1, characterized in that: The anti-aging agent is prepared by the following steps: S1. Mix 2,2,6,6-tetramethylpiperidinol, n-octane and molybdenum trioxide and stir evenly, heat to 85°C, add tert-butyl hydroperoxide aqueous solution dropwise, reflux for 8 hours, filter after the reaction is complete, add activated carbon to the filtrate and stir for 1 hour, let stand, filter, take the filtrate, and distill under reduced pressure to obtain intermediate 1; S2. After pentaerythritol and benzene are mixed, phosphorus trichloride is slowly added dropwise under stirring, and the temperature is controlled not to exceed 25° C. After the addition is completed, the reaction temperature is controlled to 75° C., and the reaction is refluxed for 4 hours. After the reaction is completed, distillation is performed to obtain intermediate 2; S3, mixing intermediate 2, intermediate 1, potassium carbonate and N,N-dimethylformamide, stirring evenly, reacting at 70°C for 6 hours, filtering, rotary evaporating, and then purifying by column chromatography, rotary evaporating to obtain intermediate 3; S4. Mix and stir the intermediate 3, 3-butene-1-ol, potassium carbonate and N,N-dimethylformamide evenly, react at 75°C for 8 hours, filter, rotary evaporate, purify by column chromatography, and rotary evaporate to obtain an anti-aging agent.
3. The aging-resistant piezoelectric cable according to claim 2, characterized in that: In step S1, the ratio of the amount of 2,2,6,6-tetramethylpiperidinol, n-octane, molybdenum trioxide, and tert-butyl hydroperoxide aqueous solution is 15.7 g:20.3 g:0.2 g:10 mL.
4. The aging-resistant piezoelectric cable according to claim 2, characterized in that: In step S2, the ratio of pentaerythritol, benzene and phosphorus trichloride is 13.6 g:100 mL:28.1 g.
5. The aging-resistant piezoelectric cable according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 2, intermediate 1, potassium carbonate and N,N-dimethylformamide is 27.7 g: 28.5 g: 13.8 g: 150 mL.
6. The aging-resistant piezoelectric cable according to claim 2, characterized in that: In step S4, the ratio of the amount of intermediate 3, 3-butene-1-ol, potassium carbonate, and N,N-dimethylformamide is 51.3 g:7.2 g:13.8 g:150 mL.
7. The aging-resistant piezoelectric cable according to claim 1, characterized in that: The modified magnesium hydroxide is prepared by the following steps: At room temperature, magnesium hydroxide and deionized water are stirred, γ-aminopropyltriethoxysilane is added, and stirring is continued. After the reaction is completed, the mixture is filtered and vacuum dried to obtain modified magnesium hydroxide.
8. The aging-resistant piezoelectric cable according to claim 7, characterized in that: The usage ratio of magnesium hydroxide, deionized water and γ-aminopropyltriethoxysilane is 5.0 g:100 mL:7.5 g.
Citation Information
Patent Citations
Oxidation-resistant carbon nanotube modified polyethylene composite material and preparation method thereof
CN116462900A
Cable material for automobile cable and preparation method of cable material
CN118580607A
Marine cable manufacturing and processing technology
CN118727477A
Discoloration resistant polyolefin resin composition
JP2003231779A
